2012
DOI: 10.1590/s1679-87592012000300005
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear abnormalities in erythrocytes and morphometric indexes in the catfish Cathorops spixii (Ariidae) from different sites on the southeastern Brazilian coast

Abstract: Nuclear abnormalities in erythrocytes (NAE) were taken as biomarkers in the catfish Cathorops spixii (Ariidae) sampled in an estuary little affected by human activity (Cananéia) and in three regions (Santos Channel: SC, Santos Bay: SB and São Vicente Channel: SVC) of the Santos-São Vicente estuary impacted by various anthropogenic activities. Increases in NAE were observed in fish from SC and SVC sampled in the summer period as compared with specimens from the Cananéia estuary. These results suggest the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 26 publications
2
18
0
4
Order By: Relevance
“…NAE are sensitive non-specific indicators of mutagenic damage, they can however provide an additional tool for the understanding of the genotoxic effect and have been used by some authors in biomonitoring studies [15,26,27]. In the four species analyzed (M. americanus, M. furnieri, C. faber and P. brasiliensis) in relation to the expression of genotoxic effects, C. faber was the most responsive since it showed a more significant NAE, as well as clastogenic effects expressed with a greater frequency of micronuclei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NAE are sensitive non-specific indicators of mutagenic damage, they can however provide an additional tool for the understanding of the genotoxic effect and have been used by some authors in biomonitoring studies [15,26,27]. In the four species analyzed (M. americanus, M. furnieri, C. faber and P. brasiliensis) in relation to the expression of genotoxic effects, C. faber was the most responsive since it showed a more significant NAE, as well as clastogenic effects expressed with a greater frequency of micronuclei.…”
Section: Discussionmentioning
confidence: 99%
“…The Ariidae catfish, Cathoropsspixii, has been validated as a bioindicator species for exposure to metals in natural aquatic ecosystems such as estuarine systems [13,14] and the genotoxic effects in this fish submitted to different degrees of anthropogenic influence has been observed [15]. Taking into account the potential damage to environmental conditions, no target species were pre-defined in this present study, instead all the species caught, with the exception of Cathoropsspixii (catfish) -the focus of another study [13,16] -were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, Cathorops spixii have been used as bioindicators of contamination in SSV and CAN, since they accumulate and participate in the dynamics of essential and nonessential metals, such as Zn, Cu, Mn, Fe, Hg, Pb, Cd, and Ni (Azevedo et al 2012a). Besides, C. spixii responds to biochemical, histopathological (Azevedo et al 2013), and genotoxic effects by nuclear abnormalities in erythrocytes alterations (Azevedo et al 2012b) and these studies showed greater damage to catfish from SSV than the CAN estuary.…”
Section: Introductionmentioning
confidence: 88%
“…The CIP estuarine complex has been considered uncontaminated by some authors (Azevedo et al, 2012); however, other studies have reported moderate to high concentrations of metals in sediments from the region (Cruz et al, 2014), especially close to the Valo Grande Channel (Aguiar et al, 2008;Mahiques et al, 2009;Saito, 2002;Guimarães and Sígolo, 2008b). In the northern portion of CIP estuarine complex, there is a consensus that the mining and metallurgical activities that took place in the upper parts of the RIR basin represent the main source of metals, and that the Plumbum Company was the main contributor of Pb, Cu, Zn and Cr to the system (Guimarães and Sígolo, 2008a;Piedade et al, 2014), along with a set of mines that were spread out across the region.…”
Section: Tier 0stressor Identificationmentioning
confidence: 99%